Jan Fook (2002): Social Work: Critical Theory and Practice. London: Sage, pp. 179. - Catherine McDonald (Social Work and Society)
In his recent book on the contemporary politics of social work, Powell (2001) nominates Jan Fook and Karen Healy as two Australian authors who have made significant contributions to the radical or critical social work tradition. I have chosen to review them together, as each, in different ways, attempts to achieve the same purpose. That is, they attempt to provide a convincing account for adopting a critical approach to practice in the contemporary conditions of the 21st century and, in doing so, re-invigorate the radical tradition of social work practice. My first comment, important for the readership of this international journal, is that both books easily ‘travel’ beyond the Australian context.